2011
DOI: 10.1542/peds.2011-0271
|View full text |Cite
|
Sign up to set email alerts
|

Pulse Oximetry in Pediatric Practice

Abstract: The introduction of pulse oximetry in clinical practice has allowed for simple, noninvasive, and reasonably accurate estimation of arterial oxygen saturation. Pulse oximetry is routinely used in the emergency department, the pediatric ward, and in pediatric intensive and perioperative care. However, clinically relevant principles and inherent limitations of the method are not always well understood by health care professionals caring for children. The calculation of the percentage of arterial oxyhemoglobin is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
167
2
17

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(193 citation statements)
references
References 133 publications
3
167
2
17
Order By: Relevance
“…Non-invasive haemoglobin measurements not only depend on haemoglobin concentrations, but may be influenced by peripheral perfusion, hypothermia, cardiac output, shock -and drug-induced vasoconstriction, high bilirubin concentrations and severe anaemiawhich could play a role in the emergency room [5,33,34]. Recent studies have in fact shown that the correlation between SpHb and LHb is reduced in patients with significant haemorrhage or at risk of haemorrhage [4,25,35].…”
Section: Discussionmentioning
confidence: 99%
“…Non-invasive haemoglobin measurements not only depend on haemoglobin concentrations, but may be influenced by peripheral perfusion, hypothermia, cardiac output, shock -and drug-induced vasoconstriction, high bilirubin concentrations and severe anaemiawhich could play a role in the emergency room [5,33,34]. Recent studies have in fact shown that the correlation between SpHb and LHb is reduced in patients with significant haemorrhage or at risk of haemorrhage [4,25,35].…”
Section: Discussionmentioning
confidence: 99%
“…Daha sonra SO 2 'yi hesaplamak için; oksi-Hb konsantrasyonunu, oksi-ve deoksi-Hb konsantasyonunun toplamına böler (yani; SO 2 =oksi-Hb/ Oksi-Hb+ deoksi-Hb) (Resim 1a-c, Şekil 1). 4,18 Cihazın doğru ölçüm yapabilmesi için, fotodedektör ile ışığı yayan diodların karşılıklı olması, dokunun bu iki prob arasında birbirine paralel uzanması gerekmektedir. Fotodiodlar, pulsatil veya nonpulsatil kan akımı sırasında, ışığın emilimini kaydetmek için saniyede birkaç yüz defa açılıp ka- panmaktadır.…”
Section: Nabiz Oksi̇metre Ci̇hazi Nasil çAlişir?unclassified
“…Zayıf perfüzyon, hasta hareketi, yanlış prob kullanımı nedeni ile ortaya çıkan sinyal bozuklukları, takipne, metHb, COHb ve siyanotik kalp hastalıkları, nabız oksimetre sonuçlarını yanıltabilir. 4,18,19 Nabız oksimetre okumaları sırasında, ölçüm hatalarını ortadan kaldırmak için en önemli yol; şüpheci olmaktır. Yanlış veya hatalı okuma demeden önce, hastanın klinik durumu mutlaka değer- lendirilmelidir.…”
Section: öLçüm Hatalari Ve Kisitliliklarunclassified
See 1 more Smart Citation
“…In case of jaundice treatment for the vast majority of neonates, the intense white light of phototherapy impinges the photo-detector and SpO 2 can be underestimated. This is one of the most common problems in the NICU [17]. When using pulse oximetry in the NICU under an extreme environment, it is necessary to deal with a wide dynamic range.…”
Section: Introductionmentioning
confidence: 99%